Ergonomic investigations on hand arm vibration of brush cutter for the development of a vibration reducing aid - ASWATHI K; Dr. Sureshkumar P.K (Guide) (Tavanur 2016 Kelappaji College of Agricultural Engineering and Technology)
Ergonomic investigations on hand arm vibration of brush cutter for the development of a vibration reducing aid
Ergonomic investigations on hand arm vibration of brush cutter for the development of a vibration reducing aid